Standardized documentation of drug recommendations in discharge letters - Knaup-Gregori, Petra; Pilz, Jochen; Kaltschmidt, Jens; Ludt, Sabine; Szecsenyi, Joachim; Haefeli, Walter E. (Methods of information in medicine, 2006)
Objectives: To analyze the necessity and potential usefulness of a computerized physician order entry (CPOE) system in supporting the writing of pharmacotherapeutic recommendations in discharge letters. - - Methods: Systematic analysis of drug recommendations in discharge letters of a hospital providing tertiary care, structured interviews with in-hospital prescribers, and focus groups with general practitioners who admit patients to this hospital. - - Results: We analyzed 1800 randomly selected discharge letters, 1205 of which contained pharmaco-therapeutic recommendations. The frequencies, structure, and quality of these recommendations varied considerably between departments. Nearly 16% of the recommendations contained both proprietary (brand) and non-proprietary names (active ingredient). Interviewed clinicians expressed interest in CPOE systems that check for contraindications and interactions between drugs, suggest cheaper products, and automatically insert active ingredients when omitted. The focus group sessions confirmed that the pharmacotherapeutic recommendations in current discharge letters do not effectively support daily clinical practice. - - Conclusions: Documenting active ingredients as well as brand names in drug therapy recommendations is currently not part of clinical practice. Computerized decision support can help to optimise the structure and communication of therapeutic information across interfaces and can be a quality factor with considerable influence on process quality, outcome quality, and costs of cooperative patient care.
Online: 06. Februar 2018
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 17.05.2021